On Unruly Text, or Text-Trickster: Leslie Marmon Silko’s Ceremony as Healing - Kocot, Monika (Text Matters: A Journal of Literature, Theory and Culture, 2019)
The article discusses Leslie Marmon Silko’s Ceremony with a focus on textual manifestations of the figure of the trickster. The theme of shape-shifting and transformation that one usually associates with tricksters is linked here with the theme of (non)dualist timespace, the notion of interbeing, which in turn introduces the theme of trauma healing. The author combines two perspectives—Paula Gunn Allen’s view on timespace in her The Sacred Hoop, and Gerald Vizenor’s writings concerning trickster aesthetics—in order to show that the narrative structure of the novel can also be seen as an embodiment of the trickster: trickster-timespace, trickster-relation, and trickster-processuality; these three manifestations of the trickster are analyzed from the perspective of one more actualization of the trickster, that of a psychopomp, the “Guide of Souls” (which is manifested both at the level of plot and narration).